Exterior material for power storage device and power storage device using same
The exterior material for lithium-ion batteries, featuring a high-piercing-strength polyester substrate and a low-thermal-history lamination process, addresses the challenge of achieving deep drawing properties, resulting in enhanced energy density and manufacturing efficiency.
Patent Information
- Application Number
- JP2023113617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2037-01-06
AI Technical Summary
Existing exterior materials for lithium-ion batteries made of multi-layer films face challenges in achieving sufficient deep drawing properties to form recesses of desired depths, which limits the energy density of these batteries.
The exterior material consists of a specific laminated structure with a substrate layer made of a polyester film having a piercing strength of 0.6N/μm or more, and is manufactured using a thermal lamination process at a low thermal history to prevent damage to the layers and enhance deep drawing moldability.
This configuration enables the formation of sufficiently deep recesses without breaking, thereby achieving higher energy density in lithium-ion batteries while also reducing manufacturing costs and energy consumption.
Smart Images

Figure 0007658398000003 
Figure 0007658398000004 
Figure 0007658398000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an exterior material for an electricity storage device and an electricity storage device using the same. [Background technology]
[0002] Known examples of power storage devices include secondary batteries such as lithium ion batteries, nickel metal hydride batteries, and lead storage batteries, as well as electrochemical capacitors such as electric double layer capacitors. Due to the miniaturization of portable devices or the limitations of installation space, there is a demand for further miniaturization of power storage devices, and lithium ion batteries with high energy density have attracted attention. Metal cans have traditionally been used as exterior materials for lithium ion batteries, but multilayer films that are lightweight, have high heat dissipation properties, and can be produced at low cost have come to be used.
[0003] In lithium ion batteries using the above multilayer film as an exterior material, a configuration is adopted in which the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) are covered with an exterior material containing an aluminum foil layer to prevent moisture from penetrating into the battery. Lithium ion batteries using such a configuration are called aluminum laminate type lithium ion batteries.
[0004] A known example of an aluminum laminate type lithium ion battery is an embossed type lithium ion battery in which a recess is formed in a part of the exterior material by cold forming, the battery contents are accommodated in the recess, and the remaining part of the exterior material is folded back and the edges are heat sealed (see, for example, Patent Document 1). In such a lithium ion battery, the deeper the recess formed by cold forming, the more battery contents can be accommodated, and therefore the higher the energy density can be. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-101765 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, a packaging material for an electricity storage device made of a multilayer film is required to have sufficient deep draw formability to form a recess of a desired depth. An object of the present invention is to provide a packaging material for an electricity storage device having sufficient deep draw formability, and an electricity storage device using the same. [Means for solving the problem]
[0007] The present inventors have focused on the base layer constituting the multilayer film and have investigated the various physical properties of this base layer that affect the deep drawability of the multilayer film. As a result, it has been found that a multilayer film having sufficient deep drawability can be obtained by adopting a base layer having a puncture strength of a predetermined value or more. Based on this, the present inventors have completed the following invention.
[0008] In other words, the exterior packaging material for a storage battery device of the present invention (hereinafter sometimes simply referred to as "exterior packaging material") has a structure in which at least a base material layer, an adhesive layer, a metal foil layer, a sealant adhesive layer and a sealant layer are laminated in this order, and the base material layer is a layer made of a polyester film having a puncture strength of 0.6 N / μm or more.
[0009] The exterior material according to the present invention has a specific laminated structure and the puncture strength of the base material layer contained therein is 0.6 N / μm or more, thereby achieving sufficient deep drawability. The puncture strength here refers to a measurement value according to the method specified in JIS Z1707, and means the average value of five points measured at a speed of 50 mm / min using a probe with a diameter of 1.0 mm and a tip radius of 0.5 mm.
[0010] The present inventors further focused on the heat applied in the manufacturing process of the multilayer film, and investigated the manufacturing of the multilayer film with a thermal history at as low a temperature as possible (for example, about 160°C). Exterior materials made of multilayer films are manufactured through a thermal lamination process in which films are bonded together. If a multilayer film can be manufactured with a thermal history at as low a temperature as possible, it is possible to suppress damage to each layer constituting the multilayer film due to heat and to achieve energy saving in the manufacturing process. From this viewpoint, it is preferable that the base layer is a layer made of a polyester film having a stress value at 50% elongation after heat treatment at 160°C of 75 MPa or more. The "heat treatment at 160°C" referred to here means heating the base layer (polyester film) in a hot state maintained at 160°C for 30 minutes.
[0011] It is more preferable that the substrate layer is a layer made of a polyester film having a stress value of 75 MPa or more at 50% elongation after heat treatment at 200° C. An exterior material having a substrate layer that satisfies this condition is suitable for manufacturing processes that have a thermal history not only at relatively low temperatures but also at relatively high temperatures (e.g., 200° C.). Note that the "heat treatment at 200° C." referred to here means heating the substrate layer (polyester film) in a hot environment maintained at 200° C. for 30 minutes.
[0012] The exterior material for a storage battery device preferably further includes an easy-adhesion treatment layer provided between the base material layer and the adhesive layer, which can further improve the adhesion between the base material layer and the adhesive layer and can further improve the deep draw formability.
[0013] The easy-adhesion treatment layer is preferably a layer containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin, and acrylic-grafted polyester resin, which can further improve the adhesion between the base layer and the adhesive layer and can further improve the deep-draw moldability.
[0014] The packaging material for a power storage device preferably further includes a corrosion prevention treatment layer provided on both sides of the metal foil layer, thereby making it possible to suppress corrosion of the metal foil layer and to further improve adhesion between the base layer and the metal foil layer.
[0015] An example of the corrosion prevention treatment layer is a layer containing a rare earth element oxide and phosphoric acid or a phosphate. An example of the rare earth element oxide is cerium oxide. By adopting such a configuration, the adhesion between the base layer and the metal foil layer can be further improved.
[0016] The sealant layer preferably has a surface having a static friction coefficient of 0.10 to 0.30. This can further improve deep drawability. The static friction coefficient here refers to a value measured in accordance with the method specified in JIS K7125.
[0017] The present invention also provides an electricity storage device comprising a battery element including an electrode, a lead extending from the electrode, and a container that sandwiches the lead and houses the battery element, the container being formed from the exterior packaging material for an electricity storage device of the present invention with the sealant layer facing inward. In this electricity storage device, the exterior packaging material for an electricity storage device of the present invention is used as the container that houses the battery element, so that a sufficiently deep recess can be formed without causing breakage or the like. Effect of the Invention
[0018] According to the present invention, there are provided an exterior material for an electricity storage device having sufficient deep draw formability, and an electricity storage device using the same. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an embodiment of an exterior material according to the present invention. [Diagram 2] FIG. 2(a) is a perspective view showing an embossed-type packaging material obtained by processing the packaging material shown in FIG. 1, and FIG. 2(b) is a vertical sectional view taken along line bb shown in FIG. 2(a). [Diagram 3] FIG. 3(a) is an oblique view showing the state in which the exterior material shown in FIG. 1 has been prepared, FIG. 3(b) is an oblique view showing the state in which the exterior material and battery element shown in FIG. 2(a) have been prepared, FIG. 3(c) is an oblique view showing the state in which a part of the exterior material has been folded back and the end portion has been melted, and FIG. 3(d) is an oblique view showing the state in which both sides of the folded back part have been folded back upward. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are designated by the same reference numerals, and duplicated explanations will be omitted.
[0021] [Exterior materials for power storage devices] FIG. 1 is a cross-sectional view showing an embodiment of the exterior material for a power storage device of the present invention. As shown in FIG. 1, the exterior material (exterior material for a power storage device) 10 of this embodiment is a laminate in which a base layer 11, an easy-adhesion treatment layer 12 provided on one side of the base layer 11, an adhesive layer 13 provided on the opposite side of the easy-adhesion treatment layer 12 from the base layer 11, a metal foil layer 14 having corrosion prevention treatment layers 15a and 15b on both sides provided on the opposite side of the adhesive layer 13 from the easy-adhesion treatment layer 12, a sealant adhesive layer 16 provided on the opposite side of the adhesive layer 13 from the metal foil layer 14, and a sealant layer 17 provided on the opposite side of the sealant adhesive layer 16 from the metal foil layer 14 are sequentially laminated. Here, the corrosion prevention treatment layer 15a is provided on the adhesive layer 13 side of the metal foil layer 14, and the corrosion prevention treatment layer 15b is provided on the sealant adhesive layer 16 side of the metal foil layer 14. In the exterior packaging material 10, the base material layer 11 is the outermost layer, and the sealant layer 17 is the innermost layer. That is, the exterior packaging material 10 is used with the base material layer 11 facing the exterior side of the electricity storage device, and the sealant layer 17 facing the interior side of the electricity storage device. Each layer will be described below.
[0022] (Base material layer 11) The substrate layer 11 is a layer for imparting heat resistance in the pressurized heat fusion process described below when manufacturing the electricity storage device and electrolyte resistance to electrolyte leaked from other electricity storage devices to the exterior material 10, and for suppressing the occurrence of pinholes that may occur during processing or distribution. The substrate layer 11 is a layer made of a polyester film having a puncture strength of 0.6 N / μm or more. From the viewpoint of achieving higher deep-draw formability of the exterior material 10, the puncture strength of the substrate layer 11 is preferably 0.62 N / μm or more, and more preferably 0.65 N / μm or more. The upper limit of the puncture strength of the substrate layer 11 is not particularly limited, but is about 1.5 N / μm in terms of the availability of polyester films used as the substrate layer 11. The puncture strength of a polyester film usually depends on the degree of polymerization (length of the polymer) of the polyester, the manufacturing method of the polyester film, and the like. Examples of polyester films that tend to have high puncture strength include those manufactured by a tubular method, etc.
[0023] The base layer 11 is preferably a layer made of a polyester film having a ΔA represented by the following formula (1) of 10% or more and a stress value at 50% elongation (F50 stress value) after heat treatment at 160° C. of 75 MPa or more. ΔA = (breaking elongation after heat treatment at 160°C) - (breaking elongation before heat treatment at 160°C) (1)
[0024] The longitudinal and transverse directions of the base layer are aligned with the MD (machine feed direction) and TD (perpendicular to the MD) directions of the base layer. In other words, when the base layer 11 is made of a biaxially stretched film, the longitudinal and transverse directions of the test piece are aligned with either one of the two stretching directions of the film.
[0025] By adopting a base material layer 11 that satisfies the above conditions (ΔA and F50 stress value), an exterior material 10 can be obtained that has sufficient deep drawing formability and is suitable for manufacturing processes with a thermal history at a relatively low temperature (e.g., about 160°C).
[0026] In the exterior packaging material 10, by having the above ΔA of 10% or more, the base material layer 11 is less likely to break even when it is easily stretched by a smaller force due to a heat treatment at a relatively low temperature, so that deep drawing molding can be performed even after the heat treatment (for example, after a thermal lamination treatment). From this viewpoint, ΔA is preferably 14% or more, and more preferably 16% or more. Note that the upper limit of ΔA is not particularly limited, but from the viewpoint that if the base material layer 11 is easily stretched and the stress value at 50% elongation becomes too small, it becomes difficult to fulfill the role of protecting the metal foil layer 14 from molding stress, it can be about 100%.
[0027] The "breaking elongation before heat treatment at 160°C" of the base material layer 11 is preferably more than 50%, more preferably 55 to 150%, and even more preferably 55 to 125%, from the viewpoint of achieving sufficient deep draw formability of the packaging material 10. From the same viewpoint, the "breaking elongation after heat treatment at 160°C" of the base material layer 11 is preferably more than 60%, more preferably 65 to 160%, and even more preferably 65 to 135%, from the viewpoint of achieving sufficient deep draw formability of the packaging material 10.
[0028] Furthermore, in the packaging material 10, the stress value at 50% elongation of the base material layer 11 after heat treatment at 160°C is 75 MPa or more, so that when a local force is applied to the packaging material 10, the force can be dispersed, and breakage of the metal foil layer 14 during deep drawing can be suppressed. From this viewpoint, the stress value at 50% elongation after heat treatment at 160°C is preferably 80 MPa or more, and more preferably 85 MPa or more. Note that the upper limit of the stress value at 50% elongation at 160°C is not particularly limited, but from the viewpoint of molding and use, it can be about 250 MPa.
[0029] The base material layer 11 is preferably a layer made of a polyester film having a stress value of 75 MPa or more at 50% elongation after heat treatment at 200°C. By adopting a base material layer 11 that further satisfies this condition, it is possible to obtain an exterior material 10 that is suitable for manufacturing processes with thermal history at not only relatively low temperatures but also relatively high temperatures (e.g., 200°C). From this perspective, the stress value at 50% elongation at 200°C is preferably 80 MPa or more, and more preferably 85 MPa or more. The upper limit of the stress value at 50% elongation at 200°C is not particularly limited, but from the perspective of molding and use, it can be about 250 MPa.
[0030] In this embodiment, the breaking elongation and the stress value at 50% elongation are values defined as follows. That is, the base layer cut to A4 size is heated in an oven maintained at an arbitrary heat treatment temperature (160°C or 200°C) for 30 minutes, and then a tensile test (test piece shape: No. 5 dumbbell shape as specified in JIS K7127, chuck distance: 75 mm, gauge length: 25 mm, test speed: 50 mm / min) is performed at 23°C (room temperature) in four directions (0° (MD), 45°, 90° (TD), 135°) of the base layer. Then, the breaking elongation and the stress value at 50% elongation in this embodiment are calculated by taking the average of the measurement results in the four directions. The breaking elongation is a value calculated as follows. Breaking elongation (%) = {(gauge length at break - gauge length before measurement) / gauge length before measurement} x 100
[0031] The polyester resin constituting the polyester film of the base layer 11 can be any polyester resin that satisfies the above-mentioned characteristics, and examples thereof include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, copolymer polyester, etc. Among these, copolymer polyester is preferably used from the viewpoint of excellent deep-draw moldability.
[0032] The polyester film may be one obtained by either simultaneous stretching or biaxial stretching, but is preferably a biaxially stretched polyester film from the viewpoint of obtaining superior deep drawability.
[0033] Examples of the stretching method for the biaxially stretched film include a sequential biaxial stretching method, a tubular biaxial stretching method, a simultaneous biaxial stretching method, etc. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by the tubular biaxial stretching method or the simultaneous biaxial stretching method.
[0034] The thickness of the substrate layer 11 is preferably 6 to 40 μm, and more preferably 10 to 30 μm. When the thickness of the substrate layer 11 is 6 μm or more, the pinhole resistance and insulating properties of the exterior material 10 tend to be improved. If the thickness of the substrate layer 11 exceeds 40 μm, the total thickness of the exterior material 10 increases, which is undesirable because it may be necessary to reduce the electrical capacity of the battery.
[0035] (Easy adhesion treatment layer 12) The adhesion-promoting treatment layer 12 is provided on one side of the substrate layer 11 and is disposed between the substrate layer 11 and the adhesive layer 13. The adhesion-promoting treatment layer 12 is a layer for improving the adhesion between the substrate layer 11 and the adhesive layer 13, and thus improving the adhesion between the substrate layer 11 and the metal foil layer 14. The adhesion-promoting treatment layer 12 may not be provided in the exterior material 10. In that case, the surface of the substrate layer 11 on the adhesive layer 13 side may be corona-treated in order to improve the adhesion between the substrate layer 11 and the adhesive layer 13, and thus improving the adhesion between the substrate layer 11 and the metal foil layer 14.
[0036] The easy-adhesion treatment layer 12 is preferably a layer containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin, and acrylic-grafted polyester resin. The easy-adhesion treatment layer 12 can be formed, for example, by applying a coating agent containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin, and acrylic-grafted polyester resin as a main component onto one surface of the base layer 11.
[0037] <Polyester resin> As the polyester resin, from the viewpoint of adhesiveness, a copolymerized polyester in which a copolymer component is introduced to lower the glass transition temperature is preferred. From the viewpoint of coatability, the copolymerized polyester is preferably water-soluble or water-dispersible. As such a copolymerized polyester, it is preferred to use a copolymerized polyester to which at least one group selected from the group consisting of sulfonic acid groups or their alkali metal salts is bonded (hereinafter referred to as "sulfonic acid group-containing copolymerized polyester").
[0038] The sulfonic acid group-containing copolymer polyester refers to a polyester having at least one group selected from the group consisting of a sulfonic acid group or an alkali metal salt thereof bonded to a part of a dicarboxylic acid component or a glycol component, and among these, a copolymer polyester prepared using an aromatic dicarboxylic acid component containing at least one group selected from the group consisting of a sulfonic acid group or an alkali metal salt thereof in a proportion of 2 to 10 mol % based on the total acid components is preferred.
[0039] An example of such a dicarboxylic acid is preferably 5-sodium sulfoisophthalic acid. In this case, other dicarboxylic acid components include terephthalic acid, isophthalic acid, phthalic acid, p-β-oxyethoxybenzoic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-dicarboxydiphenyl, 4,4'-dicarboxybenzophenone, bis(4-carboxyphenyl)ethane, adipic acid, sebacic acid, and cyclohexane-1,4-dicarboxylic acid.
[0040] As the glycol component for producing the sulfonic acid group-containing copolymerized polyester, ethylene glycol is mainly used, and in addition, propylene glycol, butanediol, neopentyl glycol, diethylene glycol, cyclohexanedimethanol, an ethylene oxide adduct of bisphenol A, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. can be used. Among them, it is preferable to use ethylene glycol, propylene glycol, butanediol, neopentyl glycol, diethylene glycol, cyclohexanedimethanol, etc. as the copolymerization component in that the compatibility with polystyrene sulfonate is improved.
[0041] In addition, the polyester resin may be a modified polyester copolymer, for example, a block copolymer or a graft copolymer modified with polyester, urethane, epoxy, etc. In this embodiment, in order to improve the adhesion between the easy-adhesion treatment layer 12 and the base material layer 11 and the adhesive layer 13, the easy-adhesion treatment layer 12 may further contain a resin other than the polyester resin. Examples of such resins include urethane resin and acrylic resin.
[0042] <Acrylic resin> Examples of monomer components constituting the acrylic resin include alkyl acrylates and alkyl methacrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, lauryl, stearyl, cyclohexyl, phenyl, benzyl, and phenylethyl groups); hydroxyl group-containing monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, and 2-hydroxypropyl methacrylate; acrylamide, methacrylamide, N-methylacrylamide, and N-methylmethacrylate; Amide group-containing monomers such as acrylamide, N-methylolacrylamide, N-methylolmethacrylamide, N,N-dimethylolacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, and N-phenylacrylamide; amino group-containing monomers such as N,N-diethylaminoethylacrylate and N,N-diethylaminoethylmethacrylate; epoxy group-containing monomers such as glycidylacrylate and glycidylmethacrylate; and monomers containing carboxyl groups or salts thereof such as acrylic acid, methacrylic acid, and salts thereof (lithium salt, sodium salt, potassium salt, etc.). These may be used alone or copolymerized with two or more kinds. Furthermore, these may be used in combination with other monomers other than those mentioned above.
[0043] Examples of other monomers include epoxy group-containing monomers such as allyl glycidyl ether; monomers containing sulfonic acid groups or salts thereof such as styrene sulfonic acid, vinyl sulfonic acid, and salts thereof (lithium salt, sodium salt, potassium salt, ammonium salt, etc.); monomers containing carboxyl groups or salts thereof such as crotonic acid, itaconic acid, maleic acid, fumaric acid, and salts thereof (lithium salt, sodium salt, potassium salt, ammonium salt, etc.); monomers containing acid anhydrides such as maleic anhydride and itaconic anhydride; vinyl isocyanate, allyl isocyanate, styrene, vinyl methyl ether, vinyl ethyl ether, vinyl tris alkoxysilane, alkyl maleic acid monoester, alkyl fumaric acid monoester, acrylonitrile, methacrylonitrile, alkyl itaconic acid monoester, vinylidene chloride, vinyl acetate, vinyl chloride, etc. Also, modified acrylic copolymers, such as block copolymers and graft copolymers modified with polyester, urethane, and epoxy, may be used as the acrylic resin.
[0044] The glass transition point (Tg) of the acrylic resin used in the present embodiment is not particularly limited, but is preferably 0 to 90° C., and more preferably 10 to 80° C. If the Tg is low, the adhesion under high temperature and high humidity conditions may decrease, and if the Tg is high, cracks may occur during stretching. From the viewpoint of preventing these, the Tg of the acrylic resin is preferably within the above range.
[0045] In addition, the weight average molecular weight of the acrylic resin used in this embodiment is preferably 100,000 or more, more preferably 300,000 or more. If the weight average molecular weight is low, the moist heat resistance may decrease. In this embodiment, in order to improve the adhesion between the easy-adhesion treatment layer 12 and the base material layer 11 and the adhesive layer 13, the easy-adhesion treatment layer 12 may further contain a resin other than the acrylic resin. Examples of such resins include polyester resin and urethane resin.
[0046] <Polyurethane resin> The polyurethane resin is preferably an aqueous polyurethane resin. The aqueous polyurethane resin is preferably a self-emulsifying type because of its small particle size and good stability. The particle size of the aqueous polyurethane resin is preferably about 10 to 100 nm. The aqueous polyurethane resin used in this embodiment preferably has a glass transition point (Tg) of 40°C to 150°C. If the Tg is 40°C or higher, there is a tendency that blocking can be sufficiently suppressed when the coating is wound into a roll. On the other hand, if the Tg is too high compared to the drying temperature after coating, it is difficult to form a uniform film, so the Tg is preferably 150°C or lower.
[0047] In this embodiment, a crosslinking agent may be used together with the water-based polyurethane resin. As a crosslinking agent for water-based polyurethane, a general-purpose water-soluble crosslinking agent such as a water-soluble epoxy compound can be used. The water-soluble epoxy compound is a compound that is soluble in water and has two or more epoxy groups. Examples of the water-soluble epoxy compound include polyepoxy compounds obtained by etherifying 1 mole of glycols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol with 2 moles of epichlorohydrin, and diepoxy compounds obtained by esterifying 1 mole of dicarboxylic acids such as phthalic acid, terephthalic acid, adipic acid, and oxalic acid with 2 moles of epichlorohydrin. However, the water-soluble epoxy compound is not limited to these.
[0048] These water-soluble crosslinking agents crosslink with the aqueous polyurethane resin, improving the water resistance and solvent resistance of the coating film, and also contributing to improving the adhesion between the easy-adhesion treatment layer 12 and the substrate layer 11 and the adhesive layer 13. In this embodiment, a resin other than the urethane resin may be further contained in order to improve the adhesion between the easy-adhesion treatment layer 12 and the substrate layer 11 and the adhesive layer 13. Examples of such resins include polyester resins and acrylic resins.
[0049] The easy-adhesion treatment layer 12 may be configured to contain, for example, the above-mentioned resin as the main component and a curing agent such as a polyfunctional isocyanate, a polyfunctional glycidyl compound, a melamine-based compound, etc. In this way, by containing the above-mentioned resin as the main component and a curing agent such as a polyfunctional isocyanate, a polyfunctional glycidyl compound, a melamine-based compound, etc., it is possible to incorporate a crosslinked structure, so that a strong easy-adhesion treatment layer 12 can be configured.
[0050] The coating agent used to form the easy-adhesion treatment layer 12 may be a solvent-based or water-based coating agent. A dispersion type (dispersion) using a water-based main agent has a large molecular weight, and improves the intermolecular cohesive force, which is effective for the adhesion between the easy-adhesion treatment layer 12 and the base material layer 11 and the adhesive layer 13.
[0051] The thickness of the easy-adhesion treatment layer 12 is preferably 0.02 to 0.5 μm, and more preferably 0.04 to 0.3 μm. When the thickness of the easy-adhesion treatment layer 12 is 0.02 μm or more, a uniform easy-adhesion treatment layer 12 is easily formed, and a more sufficient easy-adhesion effect tends to be obtained. On the other hand, when the thickness of the easy-adhesion treatment layer 12 is 0.5 μm or less, the deep drawability of the exterior packaging material 10 tends to be further improved.
[0052] (adhesive layer 13) The adhesive layer 13 is a layer that bonds the base material layer 11 and the metal foil layer 14. The adhesive layer 13 is bonded to the base material layer 11 via the easy-adhesion treatment layer 12. The adhesive layer 13 has an adhesive strength required to firmly bond the base material layer 11 and the metal foil layer 14, and also has a conformability (performance for reliably forming the adhesive layer 13 on a member without peeling even if the member deforms or expands / contracts) to suppress breakage of the metal foil layer 14 by the base material layer 11 during cold forming.
[0053] The adhesive constituting the adhesive layer 13 may be, for example, a two-liquid curing polyurethane adhesive having a base material made of a polyol such as polyester polyol, polyether polyol, or acrylic polyol, and a curing agent made of an isocyanate such as an aromatic or aliphatic isocyanate. In the above adhesive, the molar ratio (=NCO / OH) of the isocyanate group of the curing agent to the hydroxyl group of the base material is preferably 1 to 10, and more preferably 2 to 5.
[0054] After coating, the polyurethane adhesive is aged, for example, at 40°C for 4 days or more, to allow the reaction between the hydroxyl groups of the base material and the isocyanate groups of the curing agent to proceed, thereby enabling stronger adhesion between the base material layer 11 and the metal foil layer 14.
[0055] The thickness of the adhesive layer 13 is preferably from 1 to 10 μm, and more preferably from 2 to 6 μm, from the viewpoint of obtaining the desired adhesive strength, followability, processability, and the like.
[0056] (Metal foil layer 14) Examples of the metal foil layer 14 include various metal foils such as aluminum and stainless steel, and from the standpoint of processability such as moisture resistance and ductility, and cost, it is preferable that the metal foil layer 14 is an aluminum foil. The aluminum foil may be a general soft aluminum foil, but is preferably an iron-containing aluminum foil from the standpoint of excellent pinhole resistance and ductility during molding.
[0057] In the aluminum foil containing iron (100% by mass), the iron content is preferably 0.1 to 9.0% by mass, and more preferably 0.5 to 2.0% by mass. When the iron content is 0.1% by mass or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0% by mass or less, an exterior material 10 having better flexibility can be obtained.
[0058] Further, as the aluminum foil, a soft aluminum foil that has been annealed (for example, aluminum foil made of JIS 8021 material or 8079 material) is more preferable because it can impart the desired extensibility during molding.
[0059] The metal foil used in the metal foil layer 14 is preferably subjected to, for example, a degreasing treatment in order to obtain a desired electrolyte resistance. In addition, in order to simplify the manufacturing process, it is preferable that the metal foil has a surface that is not etched. As the degreasing treatment, for example, a wet type degreasing treatment or a dry type degreasing treatment can be used, but from the viewpoint of simplifying the manufacturing process, a dry type degreasing treatment is preferable.
[0060] As an example of the dry-type degreasing treatment, there is a method in which the degreasing treatment is performed by extending the treatment time in the process of annealing the metal foil. Sufficient electrolyte resistance can be obtained even with the degreasing treatment performed simultaneously with the annealing treatment performed to soften the metal foil.
[0061] The dry-type degreasing treatment may be a treatment other than the annealing treatment, such as a flame treatment or a corona treatment. Furthermore, the dry-type degreasing treatment may be a degreasing treatment in which contaminants are oxidatively decomposed and removed by active oxygen generated when a metal foil is irradiated with ultraviolet light of a specific wavelength.
[0062] As the wet-type degreasing treatment, for example, an acid degreasing treatment, an alkaline degreasing treatment, etc. can be used. As the acid used in the acid degreasing treatment, for example, an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, hydrofluoric acid, etc. can be used. These acids may be used alone or in combination of two or more. As the alkali used in the alkaline degreasing treatment, for example, sodium hydroxide, which has a high etching effect, can be used. The alkaline degreasing treatment may be performed using a weak alkaline material and a material containing a surfactant, etc. The above-described wet-type degreasing treatment can be performed by, for example, a dipping method or a spraying method.
[0063] From the viewpoints of barrier properties, pinhole resistance, and processability, the thickness of the metal foil layer 14 is preferably 9 to 200 μm, more preferably 15 to 150 μm, and even more preferably 15 to 100 μm. When the thickness of the metal foil layer 14 is 9 μm or more, the metal foil layer 14 is less likely to break even when subjected to stress during molding. When the thickness of the metal foil layer 14 is 200 μm or less, the increase in mass of the exterior material can be reduced, and a decrease in the weight energy density of the electricity storage device can be suppressed.
[0064] (Corrosion prevention treatment layers 15a, 15b) The corrosion prevention layers 15a and 15b serve to suppress corrosion of the metal foil layer 14 caused by the electrolytic solution or hydrofluoric acid generated by the reaction of the electrolytic solution with moisture. The corrosion prevention layer 15a serves to increase the adhesion between the metal foil layer 14 and the adhesive layer 13. The corrosion prevention layer 15b serves to increase the adhesion between the metal foil layer 14 and the sealant adhesive layer 16. The corrosion prevention layers 15a and 15b may be layers of the same configuration or layers of different configurations. Although FIG. 1 shows a case where the corrosion prevention layers are formed on both sides of the metal foil layer 14, the corrosion prevention layers may be formed on at least one side of the metal foil layer 14.
[0065] The corrosion prevention treatment layers 15a, 15b can be formed, for example, by carrying out a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, a chemical conversion treatment, a coating-type corrosion prevention treatment in which a coating agent having corrosion prevention properties is applied to a layer that serves as the base material of the corrosion prevention treatment layers 15a, 15b, or a corrosion prevention treatment that is a combination of these treatments.
[0066] Among the above-mentioned treatments, the degreasing treatment, the hydrothermal conversion treatment, and the anodizing treatment, particularly the hydrothermal conversion treatment and the anodizing treatment, are treatments in which the surface of the metal foil (aluminum foil) is dissolved by a treatment agent to form a metal compound (aluminum compound (boehmite, anodized aluminum)) having excellent corrosion resistance. For this reason, such treatments may be included in the definition of chemical conversion treatment in order to obtain a structure in which a co-continuous structure is formed from the metal foil layer 14 to the corrosion prevention treatment layers 15a and 15b.
[0067] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid, either alone or in combination. In addition, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound such as monosodium ammonium difluoride in the inorganic acid, it is possible to form a fluoride of a metal that is in a passive state as well as to degrease the metal foil layer 14, which is effective in terms of hydrofluoric acid resistance. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.
[0068] The hydrothermal conversion treatment may be, for example, a boehmite treatment obtained by immersing the metal foil layer 14 in boiling water to which triethanolamine has been added. The anodizing treatment may be, for example, an alumite treatment. The chemical conversion treatment may be, for example, a chromate treatment, a zirconium treatment, a titanium treatment, a vanadium treatment, a molybdenum treatment, a calcium phosphate treatment, a strontium hydroxide treatment, a cerium treatment, a ruthenium treatment, or a combination of two or more of these. It is preferable that the hydrothermal conversion treatment, the anodizing treatment, and the chemical conversion treatment are preceded by the above-mentioned degreasing treatment.
[0069] The chemical conversion treatment is not limited to a wet method, and may be, for example, a method in which a treatment agent used in the treatment is mixed with a resin component and then applied. In addition, the corrosion prevention treatment is preferably a coating type chromate treatment from the viewpoint of maximizing the effect and of waste liquid treatment.
[0070] Examples of the coating agent used in the coating-type corrosion prevention treatment in which a coating agent having corrosion prevention properties is applied include a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer. In particular, a method using a coating agent containing a rare earth element oxide sol is preferred.
[0071] The method of using a coating agent containing a rare earth element oxide sol is a pure coating-type corrosion prevention treatment, and by using this method, it is possible to impart a corrosion prevention effect to the metal foil layer 14 even with a general coating method. In addition, the layer formed using a rare earth element oxide sol has a corrosion prevention effect (inhibitor effect) for the metal foil layer 14 and is a material that is also suitable from an environmental perspective.
[0072] In the rare earth element oxide sol, fine particles of rare earth element oxide (for example, particles having an average particle size of 100 nm or less) are dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide. Among these, cerium oxide is preferable. This can further improve the adhesion with the metal foil layer 14. As the liquid dispersion medium for the rare earth element oxide sol, for example, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used. Among these, water is preferable. The rare earth element oxides contained in the corrosion prevention treatment layers 15a and 15b can be used alone or in combination of two or more.
[0073] In order to stabilize the dispersion of the rare earth element oxide particles, the rare earth element oxide sol preferably contains inorganic acids such as nitric acid, hydrochloric acid, and phosphoric acid, organic acids such as acetic acid, malic acid, ascorbic acid, and lactic acid, and salts thereof as a dispersion stabilizer. Among these dispersion stabilizers, it is particularly preferable to use phosphoric acid or a phosphate. This not only stabilizes the dispersion of the rare earth element oxide particles, but also improves adhesion between the metal foil layer 14 by utilizing the chelating ability of phosphoric acid in the application of the exterior material for lithium ion batteries, imparts electrolyte resistance by capturing metal ions eluted under the influence of hydrofluoric acid (passivation formation), and improves the cohesive force of the rare earth element oxide layer by facilitating dehydration condensation of phosphoric acid even at low temperatures. Examples of phosphoric acid or a phosphate used as a dispersion stabilizer include orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, alkali metal salts thereof, and ammonium salts thereof. Among them, condensed phosphoric acid such as trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, and ultrametaphosphoric acid, or alkali metal salts thereof and ammonium salts thereof are preferable for functioning as an exterior material for lithium ion batteries. In particular, when considering the drying film-forming properties (drying ability, amount of heat) when a coating composition containing a rare earth oxide sol is used to form a layer containing a rare earth oxide by various coating methods, an agent having excellent reactivity at low temperatures is preferred, and sodium salts are preferred in terms of excellent dehydration condensation at low temperatures. As the phosphate, a water-soluble salt is preferred. The phosphoric acid or phosphate contained in the corrosion prevention treatment layers 15a, 15b may be used alone or in combination of two or more.
[0074] The amount of phosphoric acid or a salt thereof in the rare earth element oxide sol is preferably 1 part by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of rare earth element oxide. If the amount is 1 part by mass or more, the sol is well stabilized and the function as an exterior material for a lithium ion battery is easily fulfilled. The upper limit of the amount of phosphoric acid or a salt thereof per 100 parts by mass of rare earth element oxide may be within a range that does not cause a decrease in the function of the rare earth element oxide sol, and is preferably 100 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of rare earth element oxide.
[0075] However, since the layer formed from the rare earth oxide sol is an aggregate of inorganic particles, the layer itself has low cohesive strength even after the drying and curing process. Therefore, in order to compensate for the cohesive strength of this layer, it is preferable to compound it with an anionic polymer.
[0076] Examples of the anionic polymer include polymers having a carboxy group, such as poly(meth)acrylic acid (or a salt thereof) or a copolymer obtained by copolymerizing poly(meth)acrylic acid as a main component. Examples of the copolymerization components of the copolymer include alkyl(meth)acrylate monomers (alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.); (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide (alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.), N-alkoxy(meth)acrylamide, N,N-dialkoxy(meth)acrylamide, ( Examples of the alkoxy group include a methoxy group, an ethoxy group, a butoxy group, an isobutoxy group, and the like.) Amide group-containing monomers such as N-methylol (meth)acrylamide and N-phenyl (meth)acrylamide; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; glycidyl group-containing monomers such as glycidyl (meth)acrylate and allyl glycidyl ether; silane-containing monomers such as (meth)acryloxypropyl trimethoxysilane and (meth)acryloxypropyl triethoxylane; and isocyanate group-containing monomers such as (meth)acryloxypropyl isocyanate. Other examples include styrene, α-methylstyrene, vinyl methyl ether, vinyl ethyl ether, maleic acid, alkyl maleic acid monoester, fumaric acid, alkyl fumaric acid monoester, itaconic acid, alkyl itaconic acid monoester, (meth)acrylonitrile, vinylidene chloride, ethylene, propylene, vinyl chloride, vinyl acetate, and butadiene.
[0077] The anionic polymer plays a role in improving the stability of the corrosion prevention treatment layers 15a, 15b (oxide layers) obtained using the rare earth oxide sol. This is achieved by the effect of protecting the hard and brittle oxide layer with the acrylic resin component, and the effect of capturing (cation catcher) ion contamination (especially sodium ions) derived from phosphates contained in the rare earth oxide sol. In other words, when the corrosion prevention treatment layers 15a, 15b obtained using the rare earth oxide sol contain alkali metal ions such as sodium or alkaline earth metal ions, the corrosion prevention treatment layers 15a, 15b tend to deteriorate starting from the places containing the ions. Therefore, the resistance of the corrosion prevention treatment layers 15a, 15b is improved by fixing the sodium ions and the like contained in the rare earth oxide sol with the anionic polymer.
[0078] The anti-corrosion treatment layers 15a, 15b formed by combining an anionic polymer and a rare earth oxide sol have the same anti-corrosion performance as the anti-corrosion treatment layers 15a, 15b formed by subjecting the metal foil layer 14 to a chromate treatment. The anionic polymer is preferably a structure in which a polyanionic polymer that is essentially water-soluble is crosslinked. Examples of crosslinking agents used to form the structure include compounds having an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group. It is also possible to introduce a crosslinking site having a siloxane bond using a silane coupling agent.
[0079] Examples of compounds having an isocyanate group include diisocyanates such as tolylene diisocyanate, xylylene diisocyanate or hydrogenated products thereof, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or hydrogenated products thereof, and isophorone diisocyanate; or polyisocyanates such as adducts obtained by reacting these isocyanates with polyhydric alcohols such as trimethylolpropane, biuret products obtained by reacting these isocyanates with water, or isocyanurates which are trimers; and blocked polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, or the like.
[0080] Examples of compounds having a glycidyl group include epoxy compounds obtained by reacting glycols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol with epichlorohydrin; epoxy compounds obtained by reacting polyhydric alcohols such as glycerin, polyglycerin, trimethylolpropane, pentaerythritol, and sorbitol with epichlorohydrin; and epoxy compounds obtained by reacting dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid with epichlorohydrin.
[0081] Examples of compounds having a carboxy group include various aliphatic or aromatic dicarboxylic acids, and further, poly(meth)acrylic acid and alkali (earth) metal salts of poly(meth)acrylic acid can also be used.
[0082] Examples of compounds having an oxazoline group include low molecular weight compounds having two or more oxazoline units, and when a polymerizable monomer such as isopropenyloxazoline is used, compounds obtained by copolymerizing an acrylic monomer such as (meth)acrylic acid, an alkyl (meth)acrylate, or a hydroxyalkyl (meth)acrylate.
[0083] Examples of the silane coupling agent include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-chloropropylmethoxysilane, vinyltrichlorosilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-isocyanatopropyltriethoxysilane. In particular, epoxysilane, aminosilane, and isocyanatesilane are preferred, taking into consideration their reactivity with anionic polymers.
[0084] The amount of the crosslinking agent is preferably 1 to 50 parts by mass, more preferably 10 to 20 parts by mass, relative to 100 parts by mass of the anionic polymer. When the ratio of the crosslinking agent is 1 part by mass or more relative to 100 parts by mass of the anionic polymer, the crosslinked structure is easily formed sufficiently. When the ratio of the crosslinking agent is 50 parts by mass or less relative to 100 parts by mass of the anionic polymer, the pot life of the coating liquid is improved.
[0085] The method for crosslinking the anionic polymer is not limited to the above-mentioned crosslinking agents, and may be a method for forming ionic crosslinks using titanium or zirconium compounds, etc. These materials may also be used as a coating composition for forming the corrosion prevention treatment layer 15a.
[0086] In the above-described corrosion prevention treatment layers 15a, 15b, the corrosion prevention treatment layers 15a, 15b formed by chemical conversion treatment, typically chromate treatment, are formed into a gradient structure with the metal foil layer 14 by treating the metal foil layer 14 with a chemical conversion treatment agent, particularly a mixture of hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid or salts thereof, and then reacting with a chromium-based or non-chromium-based compound to form a chemical conversion treatment layer on the metal foil layer 14. However, the above-mentioned chemical conversion treatment uses acid as the chemical conversion treatment agent, which deteriorates the working environment and corrodes the coating equipment.
[0087] On the other hand, unlike chemical conversion treatments such as chromate treatments, the coating-type corrosion prevention treatment layers 15a and 15b described above do not need to form a gradient structure with respect to the metal foil layer 14. Therefore, the properties of the coating agent are not restricted by acidity, alkalinity, neutrality, etc., and a good working environment can be realized. In addition, the chromate treatment using a chromium compound is preferable because alternatives are required from the viewpoint of environmental hygiene.
[0088] The corrosion prevention layers 15a and 15b may have a laminate structure in which a cationic polymer is further laminated, if necessary. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of polyethyleneimine and a polymer having a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is grafted onto an acrylic main skeleton, polyallylamine or a derivative thereof, and an aminophenol resin.
[0089] Examples of "polymers having carboxylic acid" that form ionic polymer complexes include polycarboxylic acid (salts), copolymers in which a comonomer is introduced into polycarboxylic acid (salts), and polysaccharides having carboxy groups. Examples of polycarboxylic acid (salts) include polyacrylic acid and ionic salts thereof. Examples of polysaccharides having carboxy groups include carboxymethylcellulose and ionic salts thereof. Examples of ionic salts include alkali metal salts and alkaline earth metal salts.
[0090] The primary amine grafted acrylic resin is a resin in which a primary amine is grafted to an acrylic main skeleton. Examples of the acrylic main skeleton include various monomers used in the above-mentioned acrylic polyol, such as poly(meth)acrylic acid. Examples of the primary amine to be grafted to the acrylic main skeleton include ethyleneimine.
[0091] As the polyallylamine or its derivatives, homopolymers or copolymers of allylamine, allylamine amide sulfate, diallylamine, dimethylallylamine, etc. can be used, and further, these amines can be used either as free amines or as stabilized products with acetic acid or hydrochloric acid. In addition, maleic acid, sulfur dioxide, etc. can be used as copolymer components. Furthermore, it is also possible to use types in which primary amines are partially methoxylated to impart thermal crosslinking properties. These cationic polymers may be used alone or in combination of two or more. As the cationic polymer, at least one selected from the group consisting of polyallylamine and its derivatives is preferred among the above.
[0092] The cationic polymer is preferably used in combination with a crosslinking agent having a functional group capable of reacting with amines / imines, such as a carboxy group, a glycidyl group, etc. As a crosslinking agent to be used in combination with the cationic polymer, a polymer having a carboxylic acid that forms an ionic polymer complex with polyethyleneimine can also be used, and examples thereof include polycarboxylic acid (salt) such as polyacrylic acid or its ionic salt, or a copolymer having a comonomer introduced therein, and polysaccharides having a carboxy group such as carboxymethylcellulose or its ionic salt.
[0093] In this embodiment, the cationic polymer is also described as one of the components constituting the corrosion prevention treatment layers 15a, 15b. The reason is that, as a result of intensive research using various compounds to impart electrolyte resistance and hydrofluoric acid resistance required for the exterior material for lithium ion batteries, it was found that the cationic polymer itself is a compound capable of imparting electrolyte resistance and hydrofluoric acid resistance. This is presumably because the cationic group captures fluorine ions (anion catcher), thereby suppressing damage to the metal foil layer 14. In addition, the cationic polymer is also very preferable in terms of improving the adhesion between the corrosion prevention treatment layer 15b and the sealant adhesive layer 16. In addition, since the cationic polymer is water-soluble like the anionic polymer described above, the water resistance can be improved by forming a crosslinked structure using the crosslinking agent. In this way, since a crosslinked structure can be formed even by using a cationic polymer, when a rare earth oxide sol is used to form the corrosion prevention treatment layers 15a, 15b, a cationic polymer may be used instead of an anionic polymer as the protective layer.
[0094] From the above, examples of combinations of the above-mentioned coating-type corrosion prevention treatments include (1) only rare earth oxide sol, (2) only anionic polymer, (3) only cationic polymer, (4) rare earth oxide sol + anionic polymer (laminated composite), (5) rare earth oxide sol + cationic polymer (laminated composite), (6) (rare earth oxide sol + anionic polymer: laminated composite) / cationic polymer (multilayered), (7) (rare earth oxide sol + cationic polymer: laminated composite) / anionic polymer (multilayered), etc. Among them, (1) and (4) to (7) are preferred, and (4) to (7) are more preferred. In addition, in the case of the corrosion prevention treatment layer 15a, since the corrosion prevention effect and the anchor effect (adhesion improvement effect) can be realized in one layer, (6) is particularly preferred. In addition, in the case of the corrosion prevention treatment layer 15b, since it is easier to maintain the electrolyte resistance on the sealant layer 17 side, (6) and (7) are particularly preferred. However, this embodiment is not limited to the above combination. For example, as an example of the selection of the corrosion prevention treatment, since the cationic polymer is a very preferable material in terms of good adhesion with the modified polyolefin resin mentioned in the explanation of the sealant adhesive layer 16 described later, when the sealant adhesive layer 16 is made of the modified polyolefin resin, it is possible to design the surface in contact with the sealant adhesive layer 16 by providing the cationic polymer (for example, the configurations (5) and (6)).
[0095] However, the corrosion prevention treatment layers 15a, 15b are not limited to the above-mentioned layers. For example, they may be formed using an agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol resin), as in the case of coating-type chromate, which is a known technology. By using such a treatment agent, it becomes possible to form a layer that has both corrosion prevention function and adhesion. In addition, in order to improve adhesion to the above-mentioned chemical conversion treatment layer (a layer formed by degreasing treatment, hydrothermal conversion treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments), it is also possible to perform a composite treatment using the above-mentioned cationic polymer and / or anionic polymer, or to laminate a cationic polymer and / or anionic polymer as a multilayer structure on a combination of these treatments. In addition, although it is necessary to consider the stability of the coating liquid, a layer that has both corrosion prevention function and adhesion can be formed by using a coating agent obtained by previously dissolving the above-mentioned rare earth oxide sol and a cationic polymer or anionic polymer into a one-component solution.
[0096] The mass per unit area of the corrosion prevention layers 15a and 15b is 0.005 to 0.200 g / m 2 The range of 0.010 to 0.100 g / m 2 More preferably, the range is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the metal foil layer 14. 2 Even if the thickness exceeds this value, the corrosion prevention function saturates and does not change much. On the other hand, when using a rare earth oxide sol, if the coating is thick, the heat used during drying may not cure sufficiently, which may result in a decrease in cohesive force. Note that the above information is given in terms of mass per unit area, but if the specific gravity is known, it is possible to convert the thickness from that.
[0097] The thickness of the corrosion prevention treatment layers 15a, 15b is preferably, for example, 10 nm to 5 μm, and more preferably 20 to 500 nm, from the viewpoints of corrosion prevention function and anchor function.
[0098] (Sealant adhesive layer 16) The sealant adhesive layer 16 is a layer that bonds the metal foil layer 14, on which the corrosion prevention treatment layer 15b is formed, to the sealant layer 17. Depending on the adhesive component that forms the sealant adhesive layer 16, the exterior packaging material 10 is roughly divided into a thermal laminate configuration and a dry laminate configuration.
[0099] The adhesive component forming the sealant adhesive layer 16 in the thermal laminate configuration is preferably an acid-modified polyolefin resin obtained by graft-modifying a polyolefin resin with an acid. The acid-modified polyolefin resin has a polar group introduced into a portion of the non-polar polyolefin resin, and therefore can firmly adhere to both the sealant layer 17 when it is made of a non-polar polyolefin resin film or the like, and the corrosion prevention treatment layer 15b, which often has polarity. In addition, the use of the acid-modified polyolefin resin improves the resistance of the exterior material 10 to the contents such as the electrolyte, and makes it easy to prevent the sealant adhesive layer 16 from deteriorating and decreasing in adhesion even if hydrofluoric acid is generated inside the battery.
[0100] Examples of the polyolefin resin of the acid-modified polyolefin resin include low-density, medium-density, and high-density polyethylene; ethylene-α-olefin copolymer; polypropylene; and propylene-α-olefin copolymer. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. In addition, the polyolefin resin may be a copolymer obtained by copolymerizing the above-mentioned with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. Examples of the acid that modifies the polyolefin resin include carboxylic acids, epoxy compounds, and acid anhydrides, and maleic anhydride is preferable. The acid-modified polyolefin resin used in the sealant adhesive layer 16 may be one type or two or more types.
[0101] The heat-laminate sealant adhesive layer 16 can be formed by extruding the above adhesive component with an extrusion device. The heat-laminate sealant adhesive layer 16 preferably has a thickness of 2 to 50 μm.
[0102] The adhesive component forming the sealant adhesive layer 16 having a dry laminate configuration may be, for example, the same adhesive as that listed for the adhesive layer 13. In this case, in order to suppress swelling due to the electrolyte and hydrolysis due to hydrofluoric acid, it is preferable to design the composition of the adhesive so that the main component has a skeleton that is difficult to hydrolyze and has a composition that can improve the crosslink density.
[0103] In order to improve the crosslink density, for example, dimer fatty acid, ester or hydrogenated product of dimer fatty acid, reduced glycol of dimer fatty acid, or reduced glycol of ester or hydrogenated product of dimer fatty acid may be added to the adhesive. The dimer fatty acid is an acid obtained by dimerizing various unsaturated fatty acids, and examples of its structure include acyclic, monocyclic, polycyclic, and aromatic ring types.
[0104] The fatty acid which is the starting material of the dimer fatty acid is not particularly limited. In addition, a dibasic acid used in a normal polyester polyol may be introduced with such a dimer fatty acid as an essential component. As a curing agent for the main agent constituting the sealant adhesive layer 16, for example, an isocyanate compound which can also be used as a chain extender for polyester polyol can be used. This increases the crosslink density of the adhesive coating film, leading to improved solubility and swelling, and also increases the urethane group concentration, which is expected to improve adhesion to the substrate.
[0105] Since the sealant adhesive layer 16 of the dry laminate configuration has a bond that is highly hydrolyzable, such as an ester group and a urethane group, in applications requiring higher reliability, it is preferable to use an adhesive component of a thermal laminate configuration as the sealant adhesive layer 16. For example, the sealant adhesive layer 16 is formed by mixing the various curing agents described above with a coating liquid obtained by dissolving or dispersing an acid-modified polyolefin resin in a solvent such as toluene or methylcyclohexane (MCH), applying the coating, and drying the mixture.
[0106] When the sealant adhesive layer 16 is formed by extrusion molding, the adhesive resin is likely to be oriented in the MD direction (extrusion direction) due to stress generated during extrusion molding. In this case, an elastomer may be blended into the sealant adhesive layer 16 to reduce the anisotropy of the sealant adhesive layer 16. As the elastomer to be blended into the sealant adhesive layer 16, for example, an olefin-based elastomer, a styrene-based elastomer, etc. can be used.
[0107] The average particle size of the elastomer is preferably a particle size that can improve the compatibility between the elastomer and the adhesive resin and improve the effect of reducing the anisotropy of the sealant adhesive layer 16. Specifically, the average particle size of the elastomer is preferably, for example, 200 nm or less.
[0108] The average particle size of the elastomer can be determined, for example, by taking an enlarged photograph of the cross section of the elastomer composition using an electron microscope, and then measuring the average particle size of the dispersed crosslinked rubber component by image analysis. The above elastomers may be used alone or in combination of two or more.
[0109] When an elastomer is blended in the sealant adhesive layer 16, the blending amount of the elastomer added to the sealant adhesive layer 16 (100 mass%) is, for example, preferably 1 to 25 mass%, more preferably 10 to 20 mass%. By making the blending amount of the elastomer 10 to 1 mass%, the compatibility with the adhesive resin is improved, and the effect of reducing the anisotropy of the sealant adhesive layer 16 tends to be improved. In addition, by making the blending amount of the elastomer 25 mass% or less, the effect of suppressing the swelling of the sealant adhesive layer 16 by the electrolyte tends to be improved.
[0110] As the sealant adhesive layer 16, for example, a dispersion type adhesive resin liquid in which an adhesive resin is dispersed in an organic solvent may be used.
[0111] In the case of a thermal laminate structure, the thickness of the sealant adhesive layer 16 is preferably 2 to 50 μm, and more preferably 20 to 40 μm. When the thickness of the sealant adhesive layer 16 is 2 μm or more, sufficient adhesive strength between the metal foil layer 14 and the sealant layer 17 is easily obtained, and when the thickness is 50 μm or less, the amount of moisture that penetrates from the end face of the exterior material into the internal battery element can be easily reduced. In addition, in the case of a dry laminate structure, the thickness of the sealant adhesive layer 16 is preferably 1 to 5 μm. When the thickness of the sealant adhesive layer 16 is 1 μm or more, sufficient adhesive strength between the metal foil layer 14 and the sealant layer 17 is easily obtained, and when the thickness is 5 μm or less, the occurrence of cracks in the sealant adhesive layer 16 can be suppressed.
[0112] (Sealant layer 17) The sealant layer 17 is a layer that provides heat sealing to the exterior material 10, and is a layer that is disposed on the inside and heat sealed when assembling the electricity storage device. Examples of the sealant layer 17 include resin films made of polyolefin resins or acid-modified polyolefin resins obtained by graft-modifying polyolefin resins with acids such as maleic anhydride. Among them, polyolefin resins that improve the barrier properties against water vapor and can configure the shape of the electricity storage device without being excessively crushed by heat sealing are preferred, and polypropylene is particularly preferred.
[0113] Examples of polyolefin resins include low-density, medium-density and high-density polyethylenes; ethylene-α-olefin copolymers; polypropylene; and propylene-α-olefin copolymers. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more kinds.
[0114] Furthermore, to each of the above types of polypropylene, i.e., random polypropylene, homopolypropylene, and block polypropylene, low crystalline ethylene-butene copolymers, low crystalline propylene-butene copolymers, terpolymers consisting of a three-component copolymer of ethylene, butene, and propylene, antiblocking agents (AB agents) such as silica, zeolite, and acrylic resin beads, and fatty acid amide-based slip agents may be added.
[0115] Examples of the acid-modified polyolefin resin include those similar to those listed for the sealant adhesive layer 16 .
[0116] The sealant layer 17 may be a single layer film or a multilayer film, and may be selected according to the required function. For example, in order to provide moisture resistance, a multilayer film containing a resin such as an ethylene-cyclic olefin copolymer and polymethylpentene can be used.
[0117] The sealant layer 17 may also contain various additives such as a flame retardant, a lubricant, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0118] When a heat-sealable film formed by extrusion molding is used as the sealant layer 17, the heat-sealable film tends to be oriented in the extrusion direction. For this reason, an elastomer may be blended into the heat-sealable film from the viewpoint of mitigating the anisotropy of the sealant layer 17 due to the orientation. This makes it possible to suppress whitening of the sealant layer 17 when the exterior material 10 is cold-molded to form recesses.
[0119] The elastomer constituting the sealant layer 17 may be, for example, the same material as the material exemplified as the elastomer constituting the sealant adhesive layer 16. When the sealant layer 17 has a multilayer film structure, at least one of the layers constituting the multilayer film structure may be configured to contain an elastomer. For example, when the sealant layer 17 has a three-layer laminate structure consisting of a laminated random polypropylene layer / block polypropylene layer / random polypropylene layer, the elastomer may be blended only in the block polypropylene layer, only in the random polypropylene layer, or both in the random polypropylene layer and the block polypropylene layer.
[0120] The sealant layer 17 preferably has a surface (the innermost surface of the packaging material 10) with a static friction coefficient of 0.10 to 0.30. The static friction coefficient of the above surface of the sealant layer 17 is more preferably 0.12 to 0.25. This can further improve the deep drawability. More specifically, when forming a recess in the packaging material 10 by cold forming, it is possible to prevent the side or corner of the recess, which has a high elongation rate, from being stretched more than necessary in the packaging material 10. This can prevent peeling between the metal foil layer 14 and the sealant adhesive layer 16, and prevent breakage and whitening due to cracks from occurring between the sealant layer 17 and the sealant adhesive layer 16.
[0121] In order to set the static friction coefficient of the surface of the sealant layer 17 within the above range, a lubricant may be contained in the sealant layer 17, or a lubricant may be applied to the surface of the sealant layer 17. Examples of lubricants include erucic acid amide, oleic acid amide, lauric acid amide, palmitic acid amide, stearic acid amide, ethylene bis erucic acid amide, ethylene bis oleic acid amide, methylene bis stearic acid amide, ethylene bis capric acid amide, ethylene bis lauric acid amide, and ethylene bis stearic acid amide. When the sealant layer 17 contains a lubricant, the content of the lubricant in the sealant layer 17 (100% by mass) is preferably 0.001 to 0.5% by mass. When the content of the lubricant is 0.001% by mass or more, there is a tendency that whitening of the sealant layer 17 during cold forming can be more effectively suppressed. Furthermore, when the lubricant content is 0.5 mass % or less, a decrease in adhesion strength between the surface of the sealant layer 17 and the surface of another layer in contact with it can be suppressed, and adhesion of the lubricant to the mold (adhesion of white powder) can be suppressed.
[0122] The thickness of the sealant layer 17 is preferably 10 to 100 μm, and more preferably 20 to 60 μm. When the thickness of the sealant layer 17 is 10 μm or more, sufficient heat seal strength can be obtained, and when the thickness is 100 μm or less, the amount of water vapor penetrating from the end of the packaging material can be reduced.
[0123] [Exterior material manufacturing method] Next, a description will be given of a method for manufacturing the packaging material 10. Note that the method for manufacturing the packaging material 10 is not limited to the following method.
[0124] An example of a method for producing the exterior packaging material 10 includes the following steps S11 to S14. Step S11: A step of forming a corrosion prevention treatment layer 15a on one surface of the metal foil layer 14, and forming a corrosion prevention treatment layer 15b on the other surface of the metal foil layer 14. Step S12: A step of forming an easy-adhesion treatment layer 12 on one surface of the base layer 11 to obtain a laminate. Step S13: A step of bonding the surface of the corrosion prevention treatment layer 15a opposite to the metal foil layer 14 to the surface of the easy-adhesion treatment layer 12 side of the laminate via an adhesive layer 13. Step S14: A step of forming a sealant layer 17 on the surface of the corrosion prevention treatment layer 15b opposite to the metal foil layer 14 via a sealant adhesive layer 16.
[0125] (Step S11) In step S11, a corrosion prevention treatment layer 15a is formed on one side of the metal foil layer 14, and a corrosion prevention treatment layer 15b is formed on the other side of the metal foil layer 14. The corrosion prevention treatment layers 15a and 15b may be formed separately, or both may be formed at the same time. Specifically, for example, a corrosion prevention treatment agent (base material of the corrosion prevention treatment layer) is applied to both sides of the metal foil layer 14, and then drying, hardening, and baking are performed in sequence to form the corrosion prevention treatment layers 15a and 15b at the same time. In addition, a corrosion prevention treatment agent may be applied to one side of the metal foil layer 14, and then drying, hardening, and baking are performed in sequence to form the corrosion prevention treatment layer 15a, and then the corrosion prevention treatment layer 15b may be formed in the same manner on the other side of the metal foil layer 14. The order of forming the corrosion prevention treatment layers 15a and 15b is not particularly limited. In addition, the corrosion prevention treatment agent may be different from or the same for the corrosion prevention treatment layer 15a and the corrosion prevention treatment layer 15b. As the corrosion inhibitor, for example, a corrosion inhibitor for coating type chromate treatment can be used. The method for coating the corrosion inhibitor is not particularly limited, and for example, a gravure coating method, a gravure reverse coating method, a roll coating method, a reverse roll coating method, a die coating method, a bar coating method, a kiss coating method, a comma coating method, etc. can be used. Note that, as the metal foil layer 14, an untreated metal foil layer may be used, or a metal foil layer that has been subjected to a degreasing treatment by a wet type degreasing treatment or a dry type degreasing treatment may be used.
[0126] (Process S12) In step S12, the easy-adhesion treatment layer 12 is formed on one side of the base layer 11. Here, an in-line coating method is described as an example of a method for forming the easy-adhesion treatment layer 12. First, an aqueous coating liquid containing a dispersion in which the resin that is the main component of the easy-adhesion treatment layer 12 is dispersed with a dispersant is prepared. Next, the aqueous coating liquid is applied to one side of a thermoplastic resin film (base material of the base layer 11) before the crystal orientation is completed. Next, the applied aqueous coating liquid is dried, and then the thermoplastic resin film is stretched at least in one axial direction.
[0127] Next, the orientation of the thermoplastic resin film is completed by heat treatment, thereby obtaining a laminate in which the easy-adhesion treatment layer 12 is formed on one surface of the base layer 11. By forming the easy-adhesion treatment layer 12 using such an in-line coating method, the adhesion between the base layer 11 and the easy-adhesion treatment layer 12 is improved. Note that the method for forming the easy-adhesion treatment layer 12 is not limited to the above method, and any method may be used. In addition, the timing for forming the easy-adhesion treatment layer 12 is not limited to the present embodiment.
[0128] (Step S13) In step S13, the surface of the corrosion prevention treatment layer 15a opposite to the metal foil layer 14 and the surface of the laminate facing the easy-adhesion treatment layer 12 are bonded together by a method such as dry lamination using an adhesive that forms an adhesive layer 13. In step S13, an aging (curing) treatment may be performed at a temperature range of room temperature to 100° C. to promote adhesion. The aging time is, for example, 1 to 10 days.
[0129] (Step S14) After step S13, a sealant layer 17 is formed on the surface of the corrosion prevention treatment layer 15b opposite to the metal foil layer 14 of the laminate in which the base layer 11, the easy adhesion treatment layer 12, the adhesive layer 13, the corrosion prevention treatment layer 15a, the metal foil layer 14, and the corrosion prevention treatment layer 15b are laminated in this order, via the sealant adhesive layer 16. The sealant layer 17 may be laminated by dry lamination, sandwich lamination, or the like, or may be laminated together with the sealant adhesive layer 16 by a co-extrusion method. From the viewpoint of improving adhesion, the sealant layer 17 is preferably laminated, for example, by sandwich lamination, or laminated together with the sealant adhesive layer 16 by a co-extrusion method, and more preferably laminated by sandwich lamination.
[0130] The above-described steps S11 to S14 result in the packaging material 10. The order of steps in the method for producing the packaging material 10 is not limited to the method of sequentially performing the above steps S11 to S14. For example, the order of the steps may be changed as appropriate, such as performing step S12 before performing step S11.
[0131] [Electricity storage device] Next, a description will be given of an electric storage device having an exterior material 10 as a container. The electric storage device has a battery element 1 including an electrode, a lead 2 extending from the electrode, and a container that sandwiches the lead 2 and accommodates the battery element 1, and the container is formed from the exterior material 10 so that the sealant layer 17 is on the inside. The container may be obtained by overlapping two exterior materials with the sealant layers 17 facing each other and heat-sealing the peripheral portion of the overlapped exterior material 10, or by folding one exterior material and overlapping it, and similarly heat-sealing the peripheral portion of the exterior material 10. The electric storage device may also have an exterior material 20 as a container. Examples of the electric storage device include secondary batteries such as lithium ion batteries, nickel-metal hydride batteries, and lead-acid batteries, and electrochemical capacitors such as electric double layer capacitors.
[0132] The leads 2 are sandwiched and sealed by the exterior material 10 that forms a container with the sealant layer 17 on the inside. The leads 2 may be sandwiched by the exterior material 10 via a tab sealant.
[0133] [Method of manufacturing the electricity storage device] Next, a method for manufacturing an electricity storage device using the above-mentioned exterior material 10 will be described. Here, an example will be described in which a secondary battery 40 is manufactured using an embossed type exterior material 30. FIG. 2 is a diagram showing the above-mentioned embossed type exterior material 30. (a) to (d) of FIG. 3 are perspective views showing a manufacturing process of a one-sided molded battery using the exterior material 10. The secondary battery 40 may be a double-sided molded battery manufactured by providing two exterior materials such as the embossed type exterior material 30 and bonding these exterior materials together while adjusting their alignment. The embossed type exterior material 30 may also be formed using the exterior material 20.
[0134] The secondary battery 40, which is a one-sided molded battery, can be manufactured, for example, by the following steps S21 to S25. Step S21: A step of preparing an exterior material 10, a battery element 1 including electrodes, and leads 2 extending from the electrodes. Step S22: A step of forming a recess 32 for disposing the battery element 1 on one surface of the exterior material 10 (see FIGS. 3(a) and 3(b)). Step S23: A step of placing the battery element 1 in the molding processing area (recess 32) of the embossed type exterior material 30, folding the embossed type exterior material 30 over so that the lid portion 34 covers the recess 32, and pressurizing and heat fusing one side of the embossed type exterior material 30 so as to sandwich the lead 2 extending from the battery element 1 (see Figures 3(b) and 3(c)). Step S24: Leaving one side other than the side that clamps lead 2, the other sides are pressure heat fused, and then electrolyte is injected from the remaining side and pressure heat fused in a vacuum state (see FIG. 3(c)). Step S25: A step of cutting the pressurized heat fusion edge portions other than the edge that holds the lead 2, and bending them toward the molding processing area (recess 32) (see FIG. 3(d)).
[0135] (Process S21) In step S21, an exterior material 10, a battery element 1 including electrodes, and a lead 2 extending from the electrodes are prepared. The exterior material 10 is prepared based on the above-described embodiment. There are no particular limitations on the battery element 1 and the lead 2, and a known battery element 1 and lead 2 can be used.
[0136] (Step S22) In step S22, a recess 32 for disposing the battery element 1 is formed on the sealant layer 17 side of the exterior material 10. The planar shape of the recess 32 is a shape that matches the shape of the battery element 1, for example, a rectangular shape in plan view. The recess 32 is formed, for example, by pressing a pressing member having a rectangular pressure surface against a part of the exterior material 10 in its thickness direction. In addition, the pressing position, i.e., the recess 32, is formed at a position biased toward one end of the exterior material 10 in the longitudinal direction from the center of the exterior material 10 cut into a rectangle. Thereby, after molding, the other end side where the recess 32 is not formed can be folded back to form a lid (lid portion 34).
[0137] More specifically, a method for forming the recesses 32 includes molding (deep drawing) using a mold. As a molding method, a method is exemplified in which a female mold and a male mold are arranged so as to have a gap equal to or greater than the thickness of the exterior material 10, and the male mold is pressed into the female mold together with the exterior material 10. The depth of the recesses 32 (amount of deep drawing) can be adjusted to a desired amount by adjusting the pressing amount of the male mold. The embossed type exterior material 30 is obtained by forming the recesses 32 in the exterior material 10. For example, the embossed type exterior material 30 has a shape as shown in FIG. 2. Here, FIG. 2(a) is a perspective view of the embossed type exterior material 30, and FIG. 2(b) is a vertical cross-sectional view taken along the line bb of the embossed type exterior material 30 shown in FIG. 2(a).
[0138] (Step S23) In step S23, the battery element 1, which is composed of a positive electrode, a separator, a negative electrode, and the like, is placed in the molding area (recess 32) of the embossed type exterior material 30. In addition, the leads 2, which extend from the battery element 1 and are joined to the positive electrode and the negative electrode, respectively, are drawn out from the molding area (recess 32). Thereafter, the embossed type exterior material 30 is folded back at approximately the center in the longitudinal direction, and overlapped so that the sealant layers 17 are on the inside, and one side of the embossed type exterior material 30 that sandwiches the lead 2 is heat-sealed under pressure. The heat-sealing under pressure is controlled under three conditions, namely, temperature, pressure, and time, and is appropriately set. The temperature of the heat-sealing under pressure is preferably equal to or higher than the temperature at which the sealant layer 17 melts.
[0139] The thickness of sealant layer 17 before heat fusion is preferably 40 to 80% of the thickness of lead 2. When the thickness of sealant layer 17 is equal to or greater than the above-mentioned lower limit, the end of lead 2 tends to be sufficiently filled with the heat fusion resin, and when the thickness is equal to or less than the above-mentioned upper limit, the thickness of the end of exterior material 10 of secondary battery 40 can be appropriately suppressed, and the amount of moisture penetrating from the end of exterior material 10 can be reduced.
[0140] (Step S24) In step S24, pressure heat fusion is performed on the remaining sides, leaving only one side other than the side that holds the lead 2. Then, electrolyte is injected from the remaining side, and the remaining side is pressure heat fused in a vacuum state. The pressure heat fusion conditions are the same as those in step S23.
[0141] (Step S25) The edges of the heat-sealed peripheral pressurized portions other than the edges that hold the leads 2 are cut, and the sealant layer 17 that protrudes from the edges is removed. Thereafter, the heat-sealed peripheral pressurized portions are folded back toward the recessed portion 32 to form folded back portions 42, thereby obtaining the secondary battery 40.
[0142] Although preferred embodiments of the exterior material for an energy storage device and the method for manufacturing an energy storage device according to the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. EXAMPLES
[0143] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0144] (Preparation of base layer) As the base material layer 11, polyester films (all 25 μm thick) having the properties shown in Table 1 were prepared. The puncture strength was measured in accordance with the method specified in JIS 1707. More specifically, the puncture strength was determined as the average value of five points measured at a speed of 50 mm / min using a probe with a diameter of 1.0 mm and a tip radius of 0.5 mm.
[0145] In Table 1, ΔA is the value shown by the following formula (1), F50 160 indicates the stress value at 50% elongation after heat treatment at 160℃, F50 200 indicates the stress value at 50% elongation after heat treatment at 200°C. ΔA = (breaking elongation after heat treatment at 160°C) - (breaking elongation before heat treatment at 160°C) (1)
[0146] The breaking elongation and the stress value at 50% elongation were measured as follows. That is, a polyester film cut to A4 size was heated in an oven maintained at an arbitrary heat treatment temperature (160°C or 200°C) for 30 minutes, and then a tensile test (test piece shape: No. 5 dumbbell shape as specified in JIS K7127, chuck distance: 75 mm, gauge length: 25 mm, test speed: 50 mm / min) was performed at 23°C in four directions of the base layer (0° (MD), 45°, 90° (TD), 135°). Then, the breaking elongation and the stress value at 50% elongation in this embodiment were calculated by taking the average of the measurement results in the four directions. However, the breaking elongation is a value calculated as follows. Breaking elongation (%) = {(gauge length at break - gauge length before measurement) / gauge length before measurement} x 100
[0147] [Table 1]
[0148] (Preparation of Coating Agent for Forming Easy-Adhesion Treatment Layer) As a coating agent for forming an easy-adhesion treatment layer, a coating agent having the following composition was prepared. Coating agent: Toa Gosei Co., Ltd.'s water-soluble polyester "Aronmelt PES-1000," Nihon Polyurethane Industry Co., Ltd.'s self-emulsifying polyisocyanate "Aquanate 100" and Nippon Shokubai Chemical Industry Co., Ltd.'s spherical silica particles "Seahoster KE-P30" (average particle size 0.3 μm) were added in a mixing ratio (mass ratio) of 95 / 5 / 0.5, and the mixture was diluted with water.
[0149] Example 1 In Example 1, the exterior material 10 was produced by the following method. First, a soft aluminum foil 8079 material (manufactured by Toyo Aluminum Co., Ltd.) having a thickness of 40 μm was prepared as the metal foil layer 14. Next, sodium polyphosphate-stabilized cerium oxide sol (corrosion prevention treatment agent) using distilled water as a solvent and adjusted to a solid content concentration of 10 mass % was applied by gravure coating to both sides of the metal foil layer 14. At this time, the amount of phosphoric acid was 10 parts by mass per 100 parts by mass of cerium oxide.
[0150] Next, the applied sodium polyphosphate-stabilized cerium oxide sol was dried, and then baking was performed to form a corrosion prevention treatment layer 15a on one side of the metal foil layer 14 and a corrosion prevention treatment layer 15b on the other side. The baking conditions were a temperature of 150° C. and a treatment time of 30 seconds.
[0151] Next, the polyester film A-1 was used as the base layer 11, and one side of the base layer 11 was subjected to a corona treatment.
[0152] Next, a polyurethane adhesive was applied as the adhesive layer 13 to the surface of the corrosion prevention treatment layer 15a of the metal foil layer 14 opposite to the metal foil layer 14. Next, the metal foil layer 14 and the corona-treated surface of the base material layer 11 were bonded via the adhesive layer 13 by a dry lamination method. Thereafter, the structure consisting of the base material layer 11, the adhesive layer 13, the corrosion prevention treatment layer 15a, the metal foil layer 14, and the corrosion prevention treatment layer 15b was left in an atmosphere at a temperature of 60°C for 6 days to perform an aging treatment. Thereafter, a total of three types of exterior materials 10 were produced, each having a dry laminate structure or a heat laminate structure, depending on the adhesive components forming the sealant adhesive layer 16, as shown below.
[0153] Dry laminate construction A polyurethane adhesive, which is made by blending polyisocyanate with acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane, was applied as the sealant adhesive layer 16 to the surface of the corrosion prevention treatment layer 15b opposite to the metal foil layer 14. Next, a 40 μm-thick polyolefin film (a non-oriented polypropylene film with the surface of the sealant adhesive layer 16 side corona-treated) which becomes the sealant layer 17 was bonded to the metal foil layer 14 via the sealant adhesive layer 16 by a dry lamination method. Thereafter, the structure consisting of the base layer 11, adhesive layer 13, corrosion prevention treatment layer 15a, metal foil layer 14, corrosion prevention treatment layer 15b, sealant adhesive layer 16, and sealant layer 17 was left in an atmosphere at a temperature of 40° C. for 6 days to perform aging treatment. In this way, an exterior material 10 was produced. -Heat laminated structure (160℃ or 200℃) The sealant adhesive layer 16 was formed by extruding maleic anhydride modified polypropylene (manufactured by Mitsui Chemicals, Inc., product name: Admer) which was the base material of the sealant adhesive layer 16. At this time, the thickness of the sealant adhesive layer 16 was set to 15 μm. Then, by sandwich lamination instead of dry lamination, a polyolefin film (a non-oriented polypropylene film with the surface of the sealant adhesive layer 16 side corona-treated) having a thickness of 30 μm which was to become the sealant layer 17 was bonded (heat-pressed) to the corrosion prevention treatment layer 15b via the sealant adhesive layer 16 at 160° C. or 200° C. In this way, the exterior material 10 was produced.
[0154] (Examples 2 to 6, 11, and 12 and Comparative Examples 1 to 5) Except for using the polyester films shown in Table 1 instead of the polyester film A-1, an exterior material 10 was produced in the same manner as in Example 1.
[0155] Example 7 An exterior material 10 was produced in the same manner as in Example 1, except that instead of corona-treating one side of the base layer 11, an easy-adhesion treatment layer 12 was formed on the surface of the base layer 11 facing the adhesive layer 13, and the polyester film A-3 was used instead of the polyester film A-1. The easy-adhesion treatment layer 12 was formed by applying a coating agent serving as the base material of the easy-adhesion treatment layer 12 to one side of the base layer 11 using an in-line coating method in a solid content of 0.1 g / m 2 and then dried to form an easy-adhesion treated layer 12 having a thickness of about 0.1 μm.
[0156] Example 8 Except for applying a lubricant to the surface of the sealant layer 17 (the innermost surface of the exterior material 10) to reduce the static friction coefficient and using the polyester film A-3 instead of the polyester film A-1, the exterior material 10 was produced in the same manner as in Example 1. Erucamide was used as the lubricant.
[0157] Example 9 Except for heating the exterior material 10 to 80°C for 5 days to increase the static friction coefficient of the surface of the sealant layer 17, and using the polyester film A-3 instead of the polyester film A-1, the exterior material 10 was produced in the same manner as in Example 1.
[0158] Example 10 Except for forming the corrosion prevention treatment layers 15a and 15b by chromate treatment instead of using sodium polyphosphate-stabilized cerium oxide sol, and using polyester film A-3 instead of polyester film A-1, an exterior material 10 was produced in the same manner as in Example 1. The chromate treatment was performed by applying a treatment liquid consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid to both sides of the metal foil layer 14 to form a film, and baking the film.
[0159] <Evaluation of molding depth> The molding depth at which deep-draw molding is possible for each of the three types of exterior materials 10 produced in each Example and Comparative Example was evaluated by the following method. First, the exterior material 10 was placed in a molding device so that the sealant layer 17 faced upward. The molding depth of the molding device was set to 3.5 to 7.0 mm in increments of 0.5 mm, and cold-draw molding was performed in an environment of room temperature 23°C and dew point temperature -35°C. The punch mold used had a rectangular cross section of 70 mm x 80 mm, a punch radius (RP) of 1.00 mm on the bottom, and a punch corner radius (RCP) of 1.00 mm on the side. The die mold used had a die radius (RD) of 1.00 mm on the upper surface of the opening. The presence or absence of breaks and pinholes in the cold-drawn portion was visually confirmed while irradiating the exterior material 10 with a light, and the maximum molding depth at which deep-draw molding was possible without the occurrence of either breaks or pinholes (molding limit) was obtained. The results are shown in Table 2.
[0160] <Evaluation of Adhesion> The adhesiveness between the base material layer 11 and the metal foil layer 14 of the thermally laminated exterior material 10 (160°C) produced in each of the Examples and Comparative Examples was evaluated by the following method. First, the exterior material 10 was placed in a molding device so that the sealant layer 17 faced upward. The molding depth of the molding device was set to 5 mm, and cold molding was performed in an environment of room temperature 23°C and dew point temperature -35°C. The punch mold used had a rectangular cross section of 70 mm x 80 mm, a punch radius (RP) of 1.00 mm on the bottom, and a punch corner radius (RCP) of 1.00 mm on the side. The die mold used had a die radius (RD) of 1.00 mm on the top surface of the opening.
[0161] Next, the cold-formed exterior material 10 was placed in a 100 mL beaker containing 30 mL of 1M lithium hexafluorophosphate solution (solvent volume ratio = ethyl carbonate: dimethyl carbonate: dimethyl carbonate = 1:1:1). Next, the beaker containing the exterior material 10 was sealed in a one-gallon can and placed in a temperature environment of 40 ° C. for 2 hours, thereby exposing the exterior material 10 to the electrolyte. Thereafter, the exterior material 10 was removed from the beaker in the one-gallon can and placed in an oven at 110 ° C., in an environment of temperature 60 ° C. and humidity 95%, or in warm water at 50 ° C. Then, one week, two weeks, three weeks, and four weeks later, the presence or absence of peeling between the base material layer 11 and the metal foil layer 14 of the exterior material 10 was visually confirmed, and the maximum period (unit: week) during which peeling was not confirmed between the base material layer 11 and the metal foil layer 14 was obtained. Based on the results, the adhesion between the base material layer 11 and the metal foil layer 14 was evaluated according to the following evaluation criteria. The results are shown in Table 2. For Comparative Examples 3 to 5, the molding limit was less than 5 mm, so the adhesion was not evaluated. A: No peeling was observed even after 4 weeks. B: No peeling was observed after 3 weeks, but peeling occurred after 4 weeks.
[0162] <Evaluation of face powder> For the exterior materials with a thermal laminate structure (160°C) produced in each Example and Comparative Example, a molding device capable of cold molding with a drawn portion of 70 mm x 80 mm was used, and cold molding was performed 10,000 times in succession with a drawing depth of 5 mm. After this state, it was confirmed whether there was any adhesion due to mold dirt on the exterior materials due to cold molding. Note that evaluation was not performed for those with a forming limit of less than 5 mm. A: After 10,000 cycles, no adhesions to the cold-formed exterior material could be visually confirmed, and even when cold-forming was performed 15,000 times continuously without cleaning the mold, no adhesions to the cold-formed exterior material could be visually confirmed. B: After 10,000 cycles, no adhesions were found on the cold-formed exterior material. However, when cold-forming was performed 15,000 times continuously without cleaning the mold, adhesions caused by mold dirt on the cold-formed exterior material could be visually confirmed.
[0163] [Table 2] [Explanation of symbols]
[0164] 1...battery element, 2...lead, 10...exterior material (exterior material for electricity storage device), 11...base material layer, 12...easy-adhesion treatment layer, 13...adhesive layer, 14...metal foil layer, 15a, 15b...corrosion prevention treatment layer, 16...sealant adhesive layer, 17...sealant layer, 30...embossed-type exterior material, 32...molded area (recess), 34...lid portion, 40...secondary battery.
Claims
1. A structure in which at least a base layer, an adhesive layer, a metal foil layer, a sealant adhesive layer, and a sealant layer are laminated in this order, The base layer is a layer made of a polyester film, The polyester film has a puncture strength of 0.6 N / μm or more, and after being heated in a hot state at 160° C. for 30 minutes, has a breaking elongation of more than 60% and a stress value at 50% elongation of 75 MPa or more; The breaking elongation and the stress value at 50% elongation are both average values of measured values in four directions of the polyester film measured by a tensile test performed under conditions of a chuck distance of 75 mm, a gauge length of 25 mm, and a test speed of 50 mm / min; The sample to be subjected to the tensile test is a No. 5 dumbbell-shaped sample as defined in JIS K7127 and is made of the polyester film. The four directions are two directions, namely, the MD direction and the TD direction of the polyester film, and two directions rotated 45° from the MD direction and the TD direction, respectively.
2. 2 . The packaging material for a power storage device according to claim 1 , wherein the base layer is a layer made of a polyester film having a stress value at 50% elongation after heat treatment at 200° C. of 75 MPa or more.
3. The exterior material for a power storage device according to claim 1 or 2, further comprising an adhesion-improving treatment layer provided between the base material layer and the adhesive layer.
4. The packaging material for a power storage device according to any one of claims 1 to 3, further comprising anti-corrosion treatment layers provided on both sides of the metal foil layer.
5. The exterior packaging material for a power storage device according to any one of claims 1 to 4, wherein the sealant layer has a surface having a static friction coefficient of 0.10 to 0.
30.
6. The battery includes a battery element including an electrode, a lead extending from the electrode, and a container that holds the lead and accommodates the battery element; The container is formed from the exterior packaging material for an electricity storage device according to any one of claims 1 to 5, with the sealant layer facing inside.
Citation Information
Patent Citations
Polyester film for battery outer packaging and element for battery outer packaging
JP2011204674A
Packaging material for lithium ion battery
JP2012124067A
Packaging material for lithium ion battery
JP2012124068A
External facing material for power storage device
JP2013101765A
Polyester film and method for producing the same
JP2013256110A